2017
DOI: 10.1186/s12882-017-0610-x
|View full text |Cite|
|
Sign up to set email alerts
|

Screening for chronic kidney disease of uncertain aetiology in Sri Lanka: usability of surrogate biomarkers over dipstick proteinuria

Abstract: BackgroundThe use of dipstick proteinuria to screen Chronic Kidney Disease of uncertain aetiology (CKDu) in Sri Lanka is a recently debated matter of dispute. The aim of this study was to assess the suitability of biomarkers: serum creatinine, cystatin C and urine albumin to creatinine ratio (ACR) for screening CKDu in Sri Lanka.MethodsForty-four male CKDu patients and 49 healthy males from a CKDu-endemic region were selected. Meanwhile, 25 healthy males from a non-endemic region were selected as an absolute c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…For example, CST3 is reported to better predict the clinical outcomes of CKD than creatinine 20 . More recently, CST3 was also reported to show a higher efficacy in detecting CKDu in endemic regions 14 . On screening a set of 8 selected biomarkers, we found that not all markers perform uniformly well across all groups.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…For example, CST3 is reported to better predict the clinical outcomes of CKD than creatinine 20 . More recently, CST3 was also reported to show a higher efficacy in detecting CKDu in endemic regions 14 . On screening a set of 8 selected biomarkers, we found that not all markers perform uniformly well across all groups.…”
Section: Discussionmentioning
confidence: 78%
“…These tests are highly sensitive in the early stages of proteinuric CKD, and are cost-effective for community screening 13 . However, the applicability of these tests is limited in diagnosing early CKDu, owing to the minimally proteinuric nature of this disease 14 . Another marker, serum creatinine is a routine test for assessing renal function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance and progression of CKDu can involve non-specific symptoms, making the disease challenging to diagnose in the early, pre-clinical stages limiting the population of cases in this study to those that were in advanced stages of the disease. Studies suggest using more sensitive methods for detecting early CKDu, with measurement of microalbuminuria and functional markers such as Cyst C, creatinine or tubular proteins like RBP4, NGAL or KIM would be beneficial in capturing a greater number of early-stage CKDu cases so that exposures can be better assessed and treatment initiated earlier [64-66].…”
Section: Discussionmentioning
confidence: 99%
“…The appearance and progression of CKDu can involve non-speci c symptoms, making the disease challenging to diagnose in the early, pre-clinical stages limiting the population of cases in this study to those that were in advanced stages of the disease. Studies suggest using more sensitive methods for detecting early CKDu, with measurement of microalbuminuria and functional markers such as Cystain C, creatinine or tubular proteins like RBP4, NGAL or KIM would be bene cial in capturing a greater number of early-stage CKDu cases so that exposures can be better assessed and treatment initiated earlier [64][65][66].…”
Section: Ministry Of Health Ckdu Diagnosis Criteria Do Not Include Sementioning
confidence: 99%